2019
DOI: 10.1002/path.5288
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutation and aberrant transcripts of WWOX in a syndrome with multiple primary tumors

Abstract: Multiple primary tumors are defined by the presence of two or more independent primary tumors in the same or different organs of an individual patient. However, the underlying genetic cause for the development of multiple primary tumors is largely unknown. In the study, we report a rare case with four synchronous distinct histological cancer types in a 26 years old Chinese female. In the patient, whole‐exome sequencing identified a homozygous germline insertion mutation in WWOX which encodes the DNA repair‐rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Another study reported that germline variants (p.W606X, IVS1762-1G > A, p.T507fs, and p.T642fs) in EXT2 were found in 4 out of 1026 patients with non-small cell lung cancer [ 32 ]. Interestingly, a female patient with early-onset multiple primary tumors was reported to have a germline homozygous WWOX variant (NC_000016.9:g.79245877_79245881dup) [ 33 ]. Multiple germline variants in GATA2 predispose individuals to familial myelodysplastic/acute leukemia syndrome [ 34 , 35 ], while germline GPC3 variants are observed in Simpson-Golabi-Behmel syndrome, an overgrowth syndrome that increases the risk of developing Wilms tumor, hepatoblastoma, and neuroblastoma [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that germline variants (p.W606X, IVS1762-1G > A, p.T507fs, and p.T642fs) in EXT2 were found in 4 out of 1026 patients with non-small cell lung cancer [ 32 ]. Interestingly, a female patient with early-onset multiple primary tumors was reported to have a germline homozygous WWOX variant (NC_000016.9:g.79245877_79245881dup) [ 33 ]. Multiple germline variants in GATA2 predispose individuals to familial myelodysplastic/acute leukemia syndrome [ 34 , 35 ], while germline GPC3 variants are observed in Simpson-Golabi-Behmel syndrome, an overgrowth syndrome that increases the risk of developing Wilms tumor, hepatoblastoma, and neuroblastoma [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a 26‐year‐old patient with early occurrence of multiple primary tumors was identified with a germline homozygous insertion variant c.1425_1426insGTAAA in the 3′ UTR of WWOX (NM_016373.3). Even though multiple abnormal WWOX transcripts were detected in the patient's normal intestinal tissue, this subject did not present any neurological phenotypes (Xu et al, 2019). Further follow‐up of long‐term survivors with WOREE syndrome may provide further clinical clues whether there is an increased cancer risk.…”
Section: Discussionmentioning
confidence: 96%
“…Loss or reduced expression of WWOX has been associated with breast cancer development and progression [ 23 , 25 , 52 58 ]. As a tumor suppressor gene and a scaffold protein, WWOX plays a crucial role in regulating multiple cellular processes, including cell growth, apoptosis, DNA repair, and maintenance of genomic stability [ 34 ].…”
Section: Discussionmentioning
confidence: 99%